Discovery of misleading graph titles at many places of the traditional scientific literature - Bhattacharjee, Pramode (International Journal of Scientific World, 2017)
This paper emphasizes the urgent need of making use of well-defined self-explanatory graph title in representing a graph in graph drawing. A lot of misleading graph titles, none of which is in accordance with the traditional convention in regard to assignment of title to a graph, has been found to prevail at many places of the traditional scientific literature. With a view to ensuring quality graphing, urgent need of getting rid of those misleading graph titles with simultaneous incorporation of self-explanatory ones (following traditional convention in the said context) has also been emphasized.